1987
DOI: 10.1002/ijc.2910400623
|View full text |Cite
|
Sign up to set email alerts
|

Effects of retinoids and interferon‐gamma on cultured breast cancer cells in comparison with tumor necrosis factor alpha

Abstract: The combination of retinoic acid or tumor necrosis factor alpha (TNF-alpha) with interferon gamma (IFN-gamma) resulted in a synergistic amplification of the anti-proliferative effect of IFN-gamma on cultured breast cancer cells. Retinoic acid could be replaced by other biologically active retinoids. This synergism was also observed for the induction of 2'-5'-oligoadenylate-synthetase, an enzyme which is not expressed constitutively on BT-20 human breast cancer cells and not inducible by retinoic acid or TNF-al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1990
1990
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…The mechanism of such augmentation is being investigated. Lastly, augmentation of IFN action by RA may not be due to enhancement of IFN receptors because both in breast tumor cells and embryonic tumor cells, which differentiate in response to RA, no increase in the affinity or number of IFN receptors was noted in RA-treated cells (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of such augmentation is being investigated. Lastly, augmentation of IFN action by RA may not be due to enhancement of IFN receptors because both in breast tumor cells and embryonic tumor cells, which differentiate in response to RA, no increase in the affinity or number of IFN receptors was noted in RA-treated cells (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…[37][38][39][40] However, a recent study using high-dose 13-cis RA treatment after myeloablative therapy and autologous bone marrow transplantation showed encouraging results. 41 Since differentiation and/or growth arrest induced by RA, TPA or vitamin D 3 was shown to be potentiated by IFN-␥ in several cell types, [42][43][44][45][46][47] the aim of our investigation was to determine whether IFN-␥ would synergize with RA or TPA to induce differentiation and growth inhibition in neuroblastoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…41 Studies of cell types other than neuroblastoma have demonstrated that IFN-␥ potentiates differentiation and/or growth arrest induced by RA or vitamin D 3 in acute promyelocytic leukemia and myelomonocytic tumor cells [42][43][44][45] and in mammary and cervical carcinoma cells. 46,47 This raises the question whether "differentiation therapy" for neuroblastomas can be improved by combined treatment with IFN-␥ and RA or other agents known to influence their growth and differentiation. Indeed, combined treatment with RA and IFN-␥ in 1 human neuroblastoma cell line, LA-N-5, was reported to synergistically affect differentiation, growth inhibition and N-myc expression.…”
mentioning
confidence: 99%
“…Human ovarian carcinoma cell lines were cultured under the con ditions previously described [22], CD44 surface expression was detected with a living cell radioimmunoassay as described by Grei ner et al [23]. In brief, about 25,000 cells were first seeded in 96-wcll tissue culture plates and after 24 h an attachment agent or the vehicle alone was added for incubation at 37 °C for 72 h. The culture medium was aspirated and 50 pi of E-MEM containing 10% BSA added before incubating at 37°C for 1 h. Thereafter, the plates were washed twice with E-MEM containing 1 % BSA.…”
Section: Cell Culturementioning
confidence: 99%